2011
DOI: 10.1007/s11269-011-9849-3
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Forecasting Using Wavelet-Genetic Programming and Wavelet-Neuro-Fuzzy Conjunction Models

Abstract: Forecasting precipitation as a major component of the hydrological cycle is of primary importance in water resources engineering, planning and management as well as in scheduling irrigation practices. In the present study the abilities of hybrid wavelet-genetic programming [i.e. wavelet-gene-expression programming, WGEP] and wavelet-neuro-fuzzy (WNF) models for daily precipitation forecasting are investigated. In the first step, the single genetic programming (GEP) and neurofuzzy (NF) models are applied to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(48 citation statements)
references
References 43 publications
0
48
0
Order By: Relevance
“…In this paper, the maximum fitness was used as stopping condition of the developed GEP models. Many researchers [26] depend on suggested values by Ferreira [27], 30 chromosomes, 8 head sizes, and 3 genes were used for model structure.…”
Section: Gene Expression Programmingmentioning
confidence: 99%
“…In this paper, the maximum fitness was used as stopping condition of the developed GEP models. Many researchers [26] depend on suggested values by Ferreira [27], 30 chromosomes, 8 head sizes, and 3 genes were used for model structure.…”
Section: Gene Expression Programmingmentioning
confidence: 99%
“…This work gave boost to similar works by other researchers. Thus Liu et al (2011) used a wavelet based approach for assessing timing errors in hydrologic predictions, while Kisi and Shiri (2011) applied Wavelet-Genetic Programming and Wavelet-NeuroFuzzy Conjunction Models for forecasting precipitation at different lead time intervals. Okkan (2012) applied NWT for monthly reservoir inflow prediction at Kemer Dam, Turkey by eliminating ineffective sub-time series through regression methods and using effective sub-time series components as new inputs to ANN.…”
Section: Applications In Hydrologymentioning
confidence: 99%
“…The study revealed that GP displayed a better edge over the other two modelling approaches in all the statistics compared like the mean absolute error (MAE), mean squared relative error (MSRE) and correlation coefficient. Kisi et al (2010) [5] developed a wavelet gene expression programming (WGEP) for forecasting daily precipitation and compared it with wavelet neuro-fuzzy models (WNF). The results showed that WGEP models are effective in forecasting daily precipitation with better performance over WNF models.…”
Section: Genetic Programming As a Modelling Toolmentioning
confidence: 99%